Improved Performance in PMCW Radar Systems Through Equalization Using Predistortion and Postprocessing - Peters, Sebastian; Faghih-Naini, Samira; Weigel, Robert; Reißland, Torsten (IEEE MTT-S International Microwave Symposium Digest, 2024)
This work presents multiple concepts for spectral equalization in pulse-modulated continuous wave (PMCW) radar systems in order to restore the received signal for improved correlation results. Two concepts for postprocessing are presented which use the spillover signal for calibration. A third concept is introduced which uses a predistorted transmit signal and thus does not require spectral equalization in the receiver. The concepts are verified through measurements using a 60 GHz transceiver together with digital-to-analog converters (DACs) and analog-to-digital converters (ADCs) operating at 4 GSa/s, resulting in a range resolution of under 4 cm.
CRIS-Team Scopus Importer:2024-08-16
Keywords: digital signal processing; millimeter wave radar; predistortion; radar signal processing